DAMPAK LOKASI, HARGA, DAN FASILITAS TERHADAP LOYALITAS PENYEWA PELAYANAN RUMAH KONSEP DI POLTEKKES SURAKARTA DIMEDIASI DENGAN KEPUASAN - anggun yurike ashari; Imronudin Imronudin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The growth of the current business has been rife. Today one of the industries that are in demand is the operation of boarding homes. Starting with the serious business area and working my way up. In order to analyze specific populations or samples, such as customers who rent out boarding homes in the Poltekkes Surakarta region, a quantitative research methodology was adopted. With a total of 150 respondents, sampling was done using a non-probability sampling technique, and the data used were primary data in the form of questionnaires. The use of Structural Equation Modeling (SEM) with SmartPLS 3.0 software aided the analysis in this study. The results of data analysis show that Location has a positive effect on Consumer Loyalty, Price has a positive effect on Consumer Loyalty, Facilities have a positive effect on Consumer Loyalty, Location has a positive effect on Consumer Satisfaction, Price has a positive effect on Consumer Satisfaction, Facilities have a positive effect on Consumer Satisfaction, Consumer Satisfaction has a positive effect as a mediation between Locations to Consumer Loyalty, Consumer Satisfaction positive effect as a mediation between Price to Consumer Loyalty, Consumer Satisfaction has a positive effect as a mediation between Facilities to Consumer Loyalty.